ANALISA DAN PERANCANGAN SISTEM PEMINJAMAN BARANG BERBASIS WEB PADA PT. SURYA KONTRUKSINDO UTAMA - Agung Hermawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In today's digital era, information technology is advancing rapidly, while computers are tools created to make human work easier. PT. Surya Kontruksindo Utama really needs a system that supports and provides convenience in the borrowing process because goods are currently being borrowed manually, so that mistakes often occur that can harm the company. This was triggered by the large number of goods owned by PT. Surya Kontruksindo Utama lost and the items returned were different by the technician from the previous borrower. In designing a system of borrowing goods at PT. Surya Kontruksindo Utama uses the waterfall method, this waterfall method was chosen because in its implementation it is carried out in stages including Planning, Analysis, Design, Implementation and Maintenance, Application for a loan system at PT. Surya Kontruksindo Utama is website-based and built with the PHP programming language and assisted by a MYSQL database, a system for lending goods to PT. Surya Kontruksindo Utama is proven to be able to solve problems and assist in managing transaction agreements made by technicians so that they can help PT. Surya Kontruksindo Utama in managing the purchasing process properly and accurately.